Income tax reform in the growth of MYPES in Los Olivos, Lima - Martínez-Aberga, Williams A. (2020)
The main objective of this study was to determine the impact of the MYPE Tax Regime on the growth of micro and small companies in the sectors, commerce, industry and services of the Olivos district in 2017. Method: The design was non-experimental, with a quantitative approach. , descriptive correlational, analytical and transversal. The population was made up of 12 MYPES from the Los Olivos district, selected according to inclusion criteria. In the data collection technique it was the survey whose instrument measured the percentage increase. Descriptive statistics were performed with measures of central tendency. The results show that in the sales sector there was a not very significant impact, due to the 4% drop in sales. At the sector level, commerce grew by 23%, assets (increased by 35%) and sales (increased by 23%), and profits significantly (increased to 105%), while the industrial sector had an impact Not significant due to the drop in income (-46%), sales (-32%) and profits (-82%). And in services, growth was moderately significant due to an increase in assets of 9%. At the sectoral level, a positive result is observed (29%): commerce (35%), industry (45%) and services (9%): Micro and small companies had some growth, increasing the personal hiring of workers. Conclusions. The Income Tax Reform had a moderately significant impact on the growth of micro and small businesses in the Los Olivos district, and its effect has been of varying magnitude in the sectors, commerce, industry and services.